Effects of Heat Generation/Absorption on a Stagnation Point Flow Past a Stretching Sheet Carbon Nanotube Water-Based Hybrid Nanofluid with Newtonian Heating - Abdul Muiz, Mohd Zaki; Nurul Farahain, Mohammad; Siti Khuzaimah, Soid; Muhammad Khairul Anuar, Mohamed; Rahimah, Jusoh (Penerbit Universiti Sultan Zainal Abidin, 2021)
This study investigates the mathematical modelling of heat generation/absorption effect on the convective flow of single wall carbon nanotube-copper (SWCNT-Cu)/water hybrid nanofluid towards a stagnation point past a stretching sheet with Newtonian heating. The set of governing equations in the form of non-linear partial differential equations are first transform using the similarity transformation technique then solved numerically by the Runge-Kutta-Fehlberg (RKF45) method in Maple software. The numerical solutions were obtained for the surface temperature, the heat transfer coefficient and the skin friction coefficient as well as the velocity and the temperature profiles. The features of the flow and heat transfer characteristics for various values of the stretching parameter, the conjugate parameter, the nanoparticle volume fraction parameter and the heat source/sink parameter are analyzed and discussed. It is found that effects of hybrid nanoparticles are more significant for lower stretching parameter and for large conjugate parameter values, as well as the heat generation/absorption.